The molecular docking of 1,4-naphthoquinone derivatives as inhibitors of Polo-like kinase 1 using Molegro Virtual Docker - Susi Kusumaningrum & , Emil Budianto, Soleh Kosela, Wahono Sumaryono, Fifit Juniarti (Journal of Applied Pharmaceutical Science, 2014)
Polo-like kinase 1 (Plk1) is over expressed in many types of human cancers, and has been implicated as an adverse prognostic marker for cancer patients. Plk1 is localized to its intracellular anchoring sites via its polo-box domain (PBD). The PBD of Plk1 has a crucial role in proper subcellular localization and mitotic functions of Plk1. Plk1 is the preferential target for inhibition of the mitotic processing therefore it can be chosen as drug target for the treatment of cancer. The aim of the study is to find plk1 inhibitor potential from naphthoquinone derivatives through binding free energy analysis into plk1 using molecular docking. We conducted docking simulation to naphthoquinone derivatives as ligands into plk1 as receptor. The 3D structure of plk1 was downloaded from PDB (Code ID:3THB). The structure of ligands and protein were prepared using ChemBioDrawUltra 12.0. Docking process, the interaction and binding of ligands – protein were done and visualized using software Molegro Virtual Docking.(MVD). The results showed no hydrogen bonding and electrostatic interaction between compound NO11(modified naphthoquinone) with Plk1, but this compound have more steric interaction with Phe 133, Asp 194, Glu 101, Lys 82, Cys 133 and Glu 140 of Plk1. Moldock scores of compound NO11, is -134.73 kcal/mol. It is predicted that compound NO11 has potency as lead compound to find a new anticancer candidates for possible therapeutic agents.
Keywords: Naphthoquinone, Polo like kinase-1, docking, molegro virtual docker.